Peningkatan Pendapatan Keluarga Melalui Pembuatan Konektor Masker Rajut pada Masa Pandemi Covid-19 - Fitri Rachmillah Fadmi; Sanatang; Jumartin Gerung (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
The covid-19 pandemic is a global health problem today. The impact of the covid-19 pandemic is evident in the community's economy. The number of occurrences of termination of employment, the implementation of Work From Home (WFH) by companies and small businesses that have gone out of business, causing the condition of family income to be low or even non-existent. This condition is felt by the people of hamlet 7 Baruga Village, Kendari City, especially housewives. The purpose of this community service is to increase family opinion through training in making Rajat mask connectors for housewives and young women. The target of this community service is 20 housewives and young women operating covid-19. This method of implementing community service uses 3 stages, namely the preparation, implementation, and evaluation stages. The results of community service provide social and economic impacts on the community in the form of increasing the skills and income of housewives and young women through the manufacture of knitted mask connectors.